Perception of screening for prostate cancer in Huánuco, Perú. 2018 - Chamorro-Jimenez, Lizeth (2019)
Objective: To determine the association between the level of knowledge, attitude, perception and factors demographic with the screening of prostate cancer in users older than 45 years attended in external office of the Urology Service Hospital health II Huánuco during the 2018. Materials and methods: observational, analytical, transversal and retrospective study. Simple random sampling was used, obtaining 424 males that met the selection criteria. For the interview was used a questionnaire organized in five parts, data demographic eight questions, screening of prostate cancer four questions with two closed and two open, knowledge fifteen questions with two options, perception fourteen Questions with two options and attitude fourteen multiple choice questions based on the Likert scale. The statistical program used was the SPSS15. Results: The mean age was 67.03 years, 70.03% had higher education degree and 60.60% was performed screening. We found statistically significant relationship between knowledge level (P=0.00), perception (P=0.04) and degree of instruction (P=0.02) with screening. No association was found between attitude (P=0.18) and screening. Those with a positive perception and high knowledge have 1.84 and 1.38 times the possibility of screening respectively. We worked with a confidence level of 95%. Conclusions: The factors associated with the screening of prostate cancer are the level of knowledge, perception and degree of instruction; the attitude is not associated.